Cerliponase Alfa for the Treatment of Atypical Phenotypes of CLN2 Disease: A Retrospective Case Series. (May 2021) - Wibbeler, Eva; Wang, Raymond; Reyes, Emily de los; Specchio, Nicola; Gissen, Paul; Guelbert, Norberto; Nickel, Miriam; Schwering, Christoph; Lehwald, Lenora; Trivisano, Marina; Lee, Laura; Amato, Gianni; et al.
Background: The classic phenotype of CLN2 disease (neuronal ceroid lipofuscinosis type 2) typically manifests between ages 2 and 4 years with a predictable clinical course marked by epilepsy, language developmental delay, and rapid psychomotor decline. Atypical phenotypes exhibit variable time of onset, symptomatology, and/or progression. Intracerebroventricular-administered cerliponase alfa (rhTPP1 enzyme) has been shown to stabilize motor and language function loss in patients with classic CLN2 disease, but its impact on individuals with atypical phenotypes has not been described. Methods: A chart review was conducted of 14 patients (8 male, 6 female) with atypical CLN2 phenotypes who received cerliponase alfa. Pre- and posttreatment CLN2 Clinical Rating Scale Motor and Language (ML) domain scores were compared. Results: Median age at first presenting symptom was 5.9 years. First reported symptoms were language abnormalities (6 [43%] patients), seizures (4 [29%]), ataxia/language abnormalities (3 [21%]), and ataxia alone (1 [7%]). Median age at diagnosis was 10.8 years. ML score declined before treatment in 13 (93%) patients. Median age at treatment initiation was 11.7 years; treatment duration ranged from 11 to 58 months. From treatment start, ML score remained stable in 11 patients (treatment duration 11-43 months), improved 1 point in 1 patient after 13 months, and declined 1 point in 2 patients after 15 and 58 months, respectively. There were 13 device-related infections in 8 patients (57%) and 10 hypersensitivity reactions in 6 (43%). Conclusions: Cerliponase alfa is well tolerated and has the potential to stabilize motor and language function in patients with atypical phenotypes of CLN2 disease.